2009
DOI: 10.1039/b814972k
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated self-assembly of dendron and dendrimer-based supramolecular liquid crystals

Abstract: A new ''inverted'' topological configuration is demonstrated both experimentally and theoretically for self-assembled dendron and dendrimer-based supramolecular liquid crystals in which the dendrons/ dendrimers occupy the continuous domain and the ionically attached pendant chains are confined in discrete domains. All previous studies on dendrimer and dendron-based liquid crystals have reported ''normal'' liquid crystalline configurations in which the dendritic templates occupy discrete domains (in spherical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
0
56
1
Order By: Relevance
“…choice of non-covalent bonding type(s), side-groups, and macromolecular template chemistry and architecture). 6 Regarding this last choice, much recent work has focused on complexes involving macromolecular templates with even more complicated architectures, such as dendrimers, 14,15 hyperbranched polymers, 16 dendronized polymers, [17][18][19] and rod-coil block copolymers. [20][21][22] Nandan et al have recently reported hierarchically organized materials formed by complexation of amphiphilic surfactants with heteroarm star (HAS) and block-arm star (BAS) polymers composed of polystyrene (PS) and poly(2-vinylpyridine) (PVP).…”
Section: Introductionmentioning
confidence: 99%
“…choice of non-covalent bonding type(s), side-groups, and macromolecular template chemistry and architecture). 6 Regarding this last choice, much recent work has focused on complexes involving macromolecular templates with even more complicated architectures, such as dendrimers, 14,15 hyperbranched polymers, 16 dendronized polymers, [17][18][19] and rod-coil block copolymers. [20][21][22] Nandan et al have recently reported hierarchically organized materials formed by complexation of amphiphilic surfactants with heteroarm star (HAS) and block-arm star (BAS) polymers composed of polystyrene (PS) and poly(2-vinylpyridine) (PVP).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Dendrons, dendrimers, and dendronized polymers have emerged as unmatched building blocks for supramolecular polymer science. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] These highly branched molecules are of unique interest because their typical size and the number of peripheral groups, which participate in supramolecular interactions, can be designed by simply changing their generation. 7 These macromolecular templates have an intrinsic "concave" curvature at the dendritic surface with respect to the focal point, which has led previous studies on the self-assembly of dendrons and dendrimerbased systems to the assumption that this concave dendrimer/ pendant chain interface is maintained in the bulk structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dendrimers of lower generation have relatively loose inner structure while higher generations are densely packed and organized. [1][2][3][4] These particular organizations result in unusual properties, as for example liquid-crystalline behavior at high concentrations, 5,6 anomalous intrinsic viscosity, 7,8 and a multivalent molecular surface. 9,10 As a consequence, dendrimers have been proposed for very useful applications, as for example, drug-delivery systems, 11,12 gene vectors, 13,14 catalysts 15,16 and organic light-emitting diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers are the more widely investigated polymers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and consist of perfectly branched molecules made of tree-like fragments (dendrons) attached to a central core. The internal organization and size of these welldefined, often monodisperse, molecules depends on the generation number, g, of dendrons.…”
Section: Introductionmentioning
confidence: 99%